High-charring low-mass A2-grade fireproof insulation board and preparation method thereof
Patent Information
- Application Number
- CN202611131053.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-07-29
AI Technical Summary
[0005]本发明的目的是针对现有聚氨酯防火保温板存在的成炭率低、热失重大、无机填料分散性差、界面结合弱、阻燃增强协同不足以及高填充条件下泡孔结构易劣化的问题,提供一种高成炭低失重A2级防火保温板及其制备方法
本发明所述的防火保温板通过含磷芳香族多元醇与芳香族聚酯多元醇共同构建高残炭聚氨酯有机基体,使材料在受热时更容易形成稳定炭化结构,降低聚氨酯基体的热分解速率和燃烧失重。
Smart Images

Figure CN122628530B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building fireproof and thermal insulation materials technology, specifically to a high-char-forming, low-weight A2 grade fireproof and thermal insulation board and its preparation method. Background Technology
[0002] With increasingly stringent requirements for building energy conservation, thermal insulation boards are being used more and more widely in building exterior walls, roofs, cold storage facilities, industrial plants, and prefabricated building envelopes. Polyurethane insulation materials are widely used in the field of thermal insulation due to their low thermal conductivity, good formability, convenient construction, and good dimensional stability. However, ordinary polyurethane materials are organic polymers that are prone to thermal decomposition, softening, shrinkage, and combustion under high temperatures or flames. This results in problems such as low char formation rate, significant mass loss, high smoke emission, and poor structural retention after combustion, making it difficult to meet the requirements for high-grade fire-resistant thermal insulation boards.
[0003] Existing technologies typically improve the flame retardant properties of polyurethane insulation materials by adding aluminum hydroxide, magnesium hydroxide, calcium carbonate, intumescent flame retardants, or inorganic fibers. However, simply increasing the amount of inorganic fillers or flame retardants can easily lead to increased system viscosity, uneven foaming, cell collapse, decreased board strength, and deteriorated thermal conductivity. Furthermore, the poor interfacial compatibility between inorganic fillers and the polyurethane organic matrix can easily cause agglomeration, sedimentation, and interfacial defects, making it difficult to simultaneously achieve flame retardancy, insulation, and mechanical properties.
[0004] Furthermore, traditional inorganic flame-retardant fillers are mostly added to polyurethane systems through physical blending, which makes it difficult to form a continuous, dense, and stable charred protective layer during heating. The lack of effective synergy between the flame-retardant components, reinforcing components, and insulating components results in problems such as weight loss, char layer cracking, rapid heat transfer, and insufficient board integrity under flame conditions. Therefore, there is an urgent need to develop a fire-resistant insulation board that combines high char formation, low weight loss, good interfacial bonding, stable cell structure, and A2 fire resistance. Summary of the Invention
[0005] The purpose of this invention is to address the problems of existing polyurethane fireproof insulation boards, such as low char formation rate, large thermal loss, poor dispersion of inorganic fillers, weak interfacial bonding, insufficient flame retardant reinforcement synergy, and easy deterioration of the cell structure under high filling conditions. This invention provides a high-char-forming, low-weight-loss A2-grade fireproof insulation board and its preparation method. This fireproof insulation board constructs a high-char-residue polyurethane organic matrix and introduces a composite reinforcing component modified by dopamine, silane coupling, and phosphorus-nitrogen flame retardant components. This allows the inorganic fillers, fiber reinforcement phase, nano-reinforcing phase, and layered barrier phase to form a stable dispersion and interfacial bonding structure within the polyurethane system, thereby improving the fireproof and flame-retardant performance, char layer stability, low weight loss performance, and structural integrity of the board.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is: a high char-forming, low-weight A2 grade fireproof and heat-insulating board, which, by weight, comprises the following raw materials: 100 parts of high char-forming polyurethane organic matrix and 44.0-52.5 parts of composite reinforcing component.
[0007] Furthermore, through the above technical solution, the high carbon residue polyurethane organic matrix is formed by reacting the following raw materials in parts by weight: 35-50 parts of aromatic polyester polyol, 20-35 parts of polyether polyol, 8-18 parts of phosphorus-containing aromatic polyol, 85-125 parts of polyphenyl polymethylene polyisocyanate, 1.0-2.5 parts of silicone oil foam stabilizer, 0.15-0.45 parts of tertiary amine catalyst, and 0.05-0.20 parts of organotin catalyst.
[0008] Furthermore, through the above technical solution, the composite reinforcing component is prepared from the following raw materials: 78-86 parts of inorganic composite filler, 8.5-11.0 parts of mineral fiber reinforcing phase, 4.0-6.5 parts of nano-inorganic reinforcing phase, 2.4-3.6 parts of layered inorganic barrier phase, 0.8-1.6 parts of dopamine hydrochloride, 1.0-2.2 parts of γ-aminopropyltriethoxysilane, 3.0-6.0 parts of ammonium polyphosphate, and 2.0-5.0 parts of melamine cyanurate.
[0009] Furthermore, through the above technical solution, the composite reinforcing component has a multi-scale inorganic skeleton structure composed of inorganic composite filler, mineral fiber reinforcing phase, nano-inorganic reinforcing phase and layered inorganic barrier phase. The surface of the multi-scale inorganic skeleton structure is sequentially formed with a polydopamine interface bonding layer, a siloxane coupling layer and an expanded carbon barrier layer composed of ammonium polyphosphate and melamine cyanurate.
[0010] Furthermore, based on the above technical solution, the preparation method of the composite reinforcing component includes the following steps: S1. The inorganic composite filler, mineral fiber reinforced phase, nano-inorganic reinforced phase and layered inorganic barrier phase are dried at 105-120℃ for 2-4 hours, cooled to 20-30℃ and then 60-90 parts of ethanol and 20-40 parts of deionized water are added. The mixture is dispersed at 800-1200 r / min for 30-60 min to obtain an inorganic multiphase dispersion.
[0011] S2. Add the dopamine hydrochloride to the inorganic multiphase dispersion, adjust the pH of the system to 8.3-8.8, and stir for 2-4 hours at 25-35℃ and 600-900r / min to obtain the dopamine-modified inorganic multiphase dispersion. S3. Add the γ-aminopropyltriethoxysilane to the dopamine-modified inorganic multiphase dispersion, adjust the pH of the system to 4.2-5.2, and stir for 2-3 hours at 55-70℃ and 700-1000r / min to obtain the reaction solution. S4. Add the ammonium polyphosphate and melamine cyanurate to the reaction solution, stir for 1-2 hours at 60-75℃ and 600-900 r / min, filter, wash the filter cake 2-3 times with ethanol, vacuum dry at 70-85℃ for 6-10 hours, pulverize and pass through an 80-120 mesh sieve to obtain the composite reinforcing component.
[0012] Further, the inorganic composite filler comprises, by weight, 35-45 parts aluminum hydroxide, 20-30 parts magnesium hydroxide, 12-22 parts light calcium carbonate, 8-16 parts wollastonite powder, and 3-8 parts hollow glass microspheres.
[0013] Furthermore, through the above technical solution, the mineral fiber reinforcing phase is one or a combination of two or more of basalt fiber, aluminosilicate fiber, and glass fiber. Furthermore, through the above technical solution, the nano-inorganic reinforcing phase is one or a combination of two or more of nano-silica, nano-alumina, and nano-boehmite.
[0014] Furthermore, through the above technical solution, the layered inorganic barrier phase is one or more of montmorillonite, mica powder, and hydrotalcite.
[0015] Furthermore, through the above technical solution, the silicone oil-based foam stabilizer is an organosilicon-polyether copolymer foam stabilizer.
[0016] Furthermore, the tertiary amine catalyst described above is one or a combination of two or more of triethylenediamine, N,N-dimethylcyclohexylamine, pentamethyldiethylenetriamine, and N,N-dimethylbenzylamine.
[0017] Furthermore, the organotin catalyst described above is one or a combination of two or more of stannous octoate, dibutyltin dilaurate, and dibutyltin diacetate.
[0018] This invention also provides a method for preparing a high-char-forming, low-weight-loss A2-grade fireproof and heat-insulating board, comprising the following steps: A1. Mix the aromatic polyester polyol, polyether polyol, phosphorus-containing aromatic polyol, silicone oil foam stabilizer, tertiary amine catalyst, organotin catalyst and 1.0-2.5 parts of deionized water at 20-30℃ and 800-1200r / min for 3-8min to obtain polyurethane component A.
[0019] A2. Add the composite reinforcing component to the polyurethane component A, and disperse it at 20-30℃ and 1000-1500r / min for 5-12min to obtain a slurry containing the composite reinforcing component A.
[0020] A3. Add the polyphenyl polymethylene polyisocyanate to the A component slurry containing the composite reinforcing component, and mix at 1500-2200 r / min for 10-25 s to obtain the foaming reaction material.
[0021] A4. Pour the foaming reaction material into the mold, foam and cure at 35-55℃ for 20-40 minutes, and after demolding, post-cur at 60-80℃ for 4-8 hours to obtain the high char-forming, low weight loss A2 grade fireproof insulation board.
[0022] Furthermore, through the above technical solution, the inner surface temperature of the mold in A4 is 35-45℃, and the casting density of the foaming reactant is controlled at 60-70 kg / m³. 3 The thickness of the sheet material obtained after demolding is 30-80mm.
[0023] Furthermore, in accordance with the above technical solution, the composite reinforcing component in A2 is added to the polyurethane component A in 2-3 portions, and after each addition, it is dispersed for 2-5 minutes at a speed of 1000-1500 r / min.
[0024] Compared with the prior art, the beneficial effects of the present invention are: The fireproof and heat-insulating board of the present invention uses phosphorus-containing aromatic polyols and aromatic polyester polyols to jointly construct a high carbon residue polyurethane organic matrix, which makes it easier for the material to form a stable carbonization structure when heated, thereby reducing the thermal decomposition rate and combustion weight loss of the polyurethane matrix.
[0025] The composite reinforcing component in the fireproof and heat-insulating board of the present invention is not a simple mixture of ordinary inorganic fillers, but a multi-scale inorganic skeleton composed of inorganic composite fillers, mineral fiber reinforcing phase, nano-inorganic reinforcing phase and layered inorganic barrier phase. It is synergistically modified by dopamine and silane coupling to form a stronger interfacial bond with the polyurethane matrix, thereby improving the filler dispersibility, cell stability and mechanical integrity of the board.
[0026] The fireproof and heat-insulating board of the present invention, through the synergistic introduction of ammonium polyphosphate and melamine cyanurate on the surface of the composite reinforcing component, enables the composite reinforcing component to promote dehydration and carbonization at high temperature, release inert gas and form an expansion barrier layer, which together with the layered inorganic barrier phase and the mineral fiber reinforcing phase to construct a continuous and dense refractory carbon layer, thereby improving the carbonization rate of the board and reducing the mass loss during the combustion process.
[0027] The mineral fiber reinforcing phase in the fireproof and heat-insulating board of the present invention can maintain the support of the carbon layer and board structure at high temperature, the nano-inorganic reinforcing phase can fill the interfacial pores and improve the dispersion state of the inorganic phase, and the layered inorganic barrier phase can extend the transfer path of heat, oxygen and combustible decomposition products, thereby achieving the synergistic effect of flame retardancy, heat insulation, reinforcement and low weight loss.
[0028] The preparation method described in this invention has clearly defined process parameters. The composite reinforcing component is first dried, dispersed, modified with dopamine, coupled with silane and compounded with phosphorus-nitrogen flame retardant components before being added to the polyurethane foaming system. This helps to reduce the agglomeration and sedimentation of inorganic fillers, improve the foaming uniformity, and make the resulting fireproof insulation board have A2 fire resistance, low thermal weight loss, high char layer stability and good thermal insulation performance. Attached Figure Description
[0029] Figure 1 This is a SEM image of the composite reinforcing component prepared in Example 1 of the present invention. Detailed Implementation
[0030] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are merely some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0031] Example 1
[0032] Preparation of a high-char-forming, low-weight-loss A2-grade fireproof and heat-insulating board: 1. Preparation of composite reinforcing components: 1.1 Mass fraction of composite reinforcing component: Raw material components: The composition includes 82.0 parts of inorganic composite filler, 9.5 parts of basalt chopped fiber, 5.2 parts of nano-silica, 3.0 parts of sodium montmorillonite, 1.2 parts of dopamine hydrochloride, 1.6 parts of γ-aminopropyltriethoxysilane, 4.5 parts of ammonium polyphosphate, 3.5 parts of melamine cyanurate, 75.0 parts of anhydrous ethanol, 30.0 parts of deionized water, 0.65 parts of 25% ammonia water, and 0.45 parts of glacial acetic acid.
[0033] The inorganic composite filler, comprising 82.0 parts by weight, is composed of the following raw materials: 36.0 parts aluminum hydroxide, 21.0 parts magnesium hydroxide, 13.0 parts light calcium carbonate, 8.5 parts wollastonite powder, and 3.5 parts hollow glass microspheres.
[0034] The composite reinforcing component has the following structural features: an inorganic flame-retardant and heat-insulating filler phase is formed by aluminum hydroxide, magnesium hydroxide, light calcium carbonate, wollastonite powder and hollow glass microspheres; a high-temperature supporting reinforcing phase is formed by basalt short-cut fibers; an interface-filling reinforcing phase is formed by nano-silica; and a layered barrier phase is formed by sodium-based montmorillonite. The surface of the above multiphase inorganic skeleton is sequentially coated with a polydopamine interface bonding layer, a siloxane coupling layer formed by γ-aminopropyltriethoxysilane, and a phosphorus-nitrogen expanded carbon barrier layer composed of ammonium polyphosphate and melamine cyanurate.
[0035] 1.2 Preparation method: S1. 36.0 parts aluminum hydroxide, 21.0 parts magnesium hydroxide, 13.0 parts light calcium carbonate, 8.5 parts wollastonite powder, 3.5 parts hollow glass microspheres, 9.5 parts basalt short-cut fibers, 5.2 parts nano silica and 3.0 parts sodium montmorillonite were dried at 110℃ for 3 hours. After drying, the mixture was cooled to 25℃. Then, 75.0 parts anhydrous ethanol and 30.0 parts deionized water were added, and the mixture was dispersed at 1000 r / min for 45 min to obtain an inorganic multiphase dispersion.
[0036] S2. Add 1.2 parts of dopamine hydrochloride to the inorganic multiphase dispersion, and add 0.65 parts of 25% ammonia solution dropwise while stirring at 750 r / min to adjust the pH of the system to 8.5; then react at 30℃ and 750 r / min for 3 h to obtain a dopamine-modified inorganic multiphase dispersion. The pH is measured every 30 min during the reaction, and controlled within the range of 8.4-8.6.
[0037] S3. Add 1.6 parts of γ-aminopropyltriethoxysilane to the dopamine-modified inorganic multiphase dispersion at a rate of 0.16 parts / min for 10 min. After the addition is complete, add 0.45 parts of glacial acetic acid dropwise to adjust the pH of the system to 4.8. Then raise the temperature to 62°C and react at 850 r / min for 2.5 h to obtain the silane coupling modified reaction solution.
[0038] S4. Add 4.5 parts of ammonium polyphosphate and 3.5 parts of melamine cyanurate to the silane coupling modification reaction solution, and react at 68℃ and 750 r / min for 1.5 h. After the reaction, filter the mixture and wash the filter cake three times with anhydrous ethanol, using 50.0 parts of anhydrous ethanol each time. Dry the washed filter cake at 80℃ and vacuum degree -0.08 MPa for 8 h. After drying, pulverize and pass through a 100-mesh sieve to obtain the composite reinforcing component.
[0039] like Figure 1As shown in the figure, the particle system exhibits an irregular, blocky, sheet-like, and locally fibrous / short rod-like interwoven distribution. The particle surfaces are rough and adhered with a large number of fine particles or flocculent deposits, indicating that the surface coating layer formed by nano-silica, polydopamine / silane coupling layer, and ammonium polyphosphate-melamine cyanurate is likely deposited on the surface of the inorganic framework. The blocky particles may correspond to inorganic flame-retardant fillers such as aluminum hydroxide, magnesium hydroxide, and light calcium carbonate; the sheet-like structure may correspond to the layered barrier phase of sodium-based montmorillonite; and the locally striped / fibrous structure may correspond to basalt short-cut fibers or wollastonite reinforcing phase. The overall morphology shows that the multiphase inorganic particles overlap, the surface is roughened, and there is a certain degree of agglomeration, which is consistent with the characteristics of composite reinforcing components treated with dopamine self-polymerization, silane coupling, and phosphorus-nitrogen flame-retardant layers.
[0040] 2. Preparation of high char-forming, low-weight-loss A2-grade fireproof and heat-insulating board: 2.1 Mass fraction of composite reinforcing component: Raw material components: The composition comprises 42.0 parts of aromatic polyester polyol, 28.0 parts of polyether polyol, 12.0 parts of phosphorus-containing aromatic polyester polyol, 105.0 parts of polyphenyl polymethylene polyisocyanate, 1.6 parts of organosilicon-polyether copolymer foam stabilizer, 0.30 parts of triethylenediamine catalyst, 0.10 parts of dibutyltin dilaurate, 1.8 parts of deionized water, and 48.0 parts of the composite reinforcing component prepared above.
[0041] The amount of the composite reinforcing component added relative to the high carbon residue polyurethane organic matrix is 48.0 parts.
[0042] The aromatic polyester polyol is Stepan's STEPANPOL. ® PS-3152.
[0043] The polyether polyol is WANOL from Wanhua Chemical. ® R4110.
[0044] The phosphorus-containing aromatic polyester polyol is halogen-free flame-retardant polyester polyol BY3009T, manufactured by Beijing Baiyuan Chemical Co., Ltd.
[0045] The polyphenyl polymethylene polyisocyanate is Wanhua Chemical's WANNATE. ® PM-200.
[0046] The organosilicon-polyether copolymer foam stabilizer is TEGOSTAB. ® B 8460.
[0047] The high carbon residue polyurethane organic matrix is formed by reacting aromatic polyester polyols, polyether polyols, phosphorus-containing aromatic polyester polyols, polyphenyl polymethylene polyisocyanates, foam stabilizers, tertiary amine catalysts, organotin catalysts and deionized water.
[0048] 2.2 Preparation method: A1. Add 42.0 parts of aromatic polyester polyol, 28.0 parts of polyether polyol, 12.0 parts of phosphorus-containing aromatic polyester polyol, 1.6 parts of organosilicon-polyether copolymer foam stabilizer, 0.30 parts of triethylenediamine catalyst, 0.10 parts of dibutyltin dilaurate and 1.8 parts of deionized water to a container and mix for 5 min at 25℃ and 1000 r / min to obtain polyurethane component A.
[0049] A2. Add 48.0 parts of the composite reinforcing component to the polyurethane component A in three separate additions, with 16.0 parts added each time. After the first addition, disperse at 1200 r / min for 3 min; after the second addition, disperse at 1200 r / min for 3 min; and after the third addition, disperse at 1400 r / min for 3 min. Then continue dispersing at 1400 r / min for 1 min to obtain the component A slurry containing the composite reinforcing component. The slurry temperature is controlled at 25 ± 2℃ during dispersion.
[0050] A3. Add 105.0 parts of polyphenyl polymethylene polyisocyanate to the A component slurry containing the composite reinforcing component at one time, and mix at 1800 r / min for 18 s to obtain the foaming reaction material.
[0051] A4. Pour the foaming reactant into a mold with an inner surface temperature of 40±2℃, according to 65kg / m³. 3 The casting density was measured and cast; after casting, it was foamed and cured at 45℃ for 30 minutes, demolded and then post-cured at 70℃ for 6 hours. After cooling to 25℃, it was cut to obtain a high-char-forming, low-weight A2 grade fireproof and heat-insulating board with a thickness of 50mm.
[0052] Example 2
[0053] The preparation of a high-char-forming, low-weight-loss A2-grade fireproof and heat-insulating board is carried out by referring to the preparation method of Example 1, except that the mass fraction of the composite reinforcing component is replaced with 44.0 parts, and the rest remains the same as in Example 1.
[0054] Example 3
[0055] The preparation of a high-char-forming, low-weight-loss A2-grade fireproof and heat-insulating board is carried out by referring to the preparation method of Example 1, except that the mass fraction of the composite reinforcing component is replaced with 52.5 parts, and the rest remains the same as in Example 1.
[0056] Example 4
[0057] The preparation of a high-char-forming, low-weight-loss A2-grade fireproof and heat-insulating board is carried out by referring to the preparation method of Example 1, except that the mineral fiber reinforcing phase is replaced with glass fiber, and the rest is the same as in Example 1.
[0058] Example 5
[0059] The preparation of a high-char-forming, low-weight A2 grade fireproof and heat-insulating board is carried out by referring to the preparation method of Example 1, except that the layered inorganic barrier phase is replaced with mica powder, and the rest is the same as in Example 1.
[0060] Comparative Example 1 The preparation of a fireproof and heat-insulating board is based on the preparation method of Example 1, except that the composite reinforcing component is replaced with an equal mass of unmodified inorganic mixed filler. The unmodified inorganic mixed filler is obtained by directly mixing aluminum hydroxide, magnesium hydroxide, light calcium carbonate, wollastonite powder, hollow glass microspheres, basalt short-cut fibers, nano-silica and sodium-based montmorillonite in the same mass proportions as in Example 1, without dopamine modification, silane coupling treatment and phosphorus-nitrogen flame retardant component composite treatment, and the rest is the same as in Example 1.
[0061] Comparative Example 2 The preparation of a fireproof and heat-insulating board is carried out according to the preparation method of Example 1, except that 1.2 parts of dopamine hydrochloride are replaced with an equal mass of deionized water, and no dopamine modification treatment is performed. The rest is the same as in Example 1.
[0062] Comparative Example 3 A fireproof and heat-insulating board was prepared by referring to the preparation method of Example 1, except that 1.6 parts of γ-aminopropyltriethoxysilane were replaced with an equal mass of anhydrous ethanol, and no silane coupling treatment was performed. The rest was the same as in Example 1.
[0063] Comparative Example 4 A fireproof and heat-insulating board was prepared by referring to the preparation method of Example 1, except that 4.5 parts of ammonium polyphosphate and 3.5 parts of melamine cyanurate were replaced with an equal mass of light calcium carbonate, and the phosphorus-nitrogen expanded carbon barrier layer was not constructed. The rest remained the same as in Example 1.
[0064] Comparative Example 5 A fireproof and heat-insulating board was prepared by referring to the preparation method of Example 1, except that 9.5 parts of basalt short-cut fibers were replaced with an equal mass of lightweight calcium carbonate, and the rest remained the same as in Example 1.
[0065] Comparative Example 6 A fireproof and heat-insulating board was prepared by referring to the preparation method of Example 1, except that 5.2 parts of nano-silica were replaced with an equal mass of ordinary micron-sized silica, and the rest remained the same as in Example 1.
[0066] Comparative Example 7 A fireproof and heat-insulating board was prepared by referring to the preparation method of Example 1, except that 3.0 parts of sodium montmorillonite were replaced with an equal mass of light calcium carbonate, and the rest remained the same as in Example 1.
[0067] Comparative Example 8 A fireproof and heat-insulating board was prepared by referring to the preparation method of Example 1, except that 82.0 parts of inorganic composite filler were replaced with an equal mass of aluminum hydroxide, and the rest remained the same as in Example 1.
[0068] Comparative Example 9 The preparation of a fireproof and heat-insulating board is carried out by referring to the preparation method of Example 1, except that 48.0 parts of the composite reinforcing component are replaced with an equal mass of ordinary aluminum hydroxide / magnesium hydroxide flame retardant filler. The ordinary aluminum hydroxide / magnesium hydroxide flame retardant filler is obtained by directly mixing 28.8 parts of aluminum hydroxide and 19.2 parts of magnesium hydroxide. The rest is the same as in Example 1.
[0069] Performance testing: (1) Combustion performance rating The test was conducted according to the A2 grade requirements in GB8624-2012 "Classification of Burning Performance of Building Materials and Products", specifically including: Non-combustibility test: Conducted according to GB / T 5464-2010 "Test Method for Non-combustibility of Building Materials". A sample with dimensions of (40±1) mm × (40±1) mm × original thickness was placed in a non-combustibility testing furnace and heated at (750±5)℃ for 30 min. The average temperature rise inside the furnace, the average temperature rise on the sample surface, the average temperature rise at the center of the sample, the average duration of the continuous flame, and the average mass loss rate of the sample were recorded. For Grade A2, the average temperature rise inside the furnace is required to be ≤50℃, the average duration of the continuous flame ≤20s, and the average mass loss rate after cooling ≤50%.
[0070] Calorific value test: The test was conducted according to GB / T14402-2007 "Determination of Calorific Value of Combustion Performance of Building Materials and Products". The total calorific value (PCS) and net calorific value (PCI) of the sample were determined using the oxygen bomb calorimetry method. The sample was crushed to a particle size of less than 0.25 mm, and after being filled with excess oxygen in the oxygen bomb and ignited, the calorific value was calculated by measuring the temperature change of the water inside the oxygen bomb. For A2 grade, the total calorific value is required to be ≤3.0 MJ / kg.
[0071] Individual combustion test: Conducted according to GB / T20284-2006 "Individual Combustion Test of Building Materials or Products". The specimen consisted of a short wing (495±5) mm × (1500±5) mm and a long wing (1000±5) mm × (1500±5) mm, mounted on a trolley and pushed into the test chamber. A propane main burner was used to generate a heat output of (30.7±2.0) kW, and the test lasted for 20 minutes. The combustion growth rate index FIGRA and the total heat release (THR) over 600 seconds were recorded and calculated. 600 Lateral flame spread (LFS) and combustion drippings. Class A2 requires FIGRA ≤ 120 W / s and THR. 600 ≤7.5MJ, and LFS < sample edge.
[0072] (2) Thermal conductivity The determination shall be performed in accordance with GB / T10294-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Thermal Insulation Materials - Protective Hot Plate Method" or GB / T10295-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Thermal Insulation Materials - Heat Flow Meter Method". In arbitration, GB / T10294-2008 shall be followed. The sample shall be processed into a plate-shaped specimen with dimensions of (300±1) mm × (300±1) mm × original thickness. It shall be placed in a protective hot plate thermal conductivity meter. Under steady-state conditions with an average temperature of (25±2) ℃ and a temperature difference of 15℃~20℃ between the two sides of the specimen, the heat flux density through the specimen, the specimen thickness, and the temperature difference between the hot and cold plates shall be measured. The thermal conductivity shall be calculated according to the formula λ=(Q×d) / (A×ΔT), where Q is the heat flux density, d is the specimen thickness, A is the heated area of the specimen, and ΔT is the temperature difference between the two sides of the specimen.
[0073] (3) Compressive strength The test was conducted according to GB / T8813-2020, "Determination of Compression Properties of Rigid Foamed Plastics". The specimens were cut into cubes with dimensions of (50±1) mm × (50±1) mm × (50±1) mm, or specimens with the original thickness and a compression surface of (50±1) mm × (50±1) mm. The specimens were placed between the upper and lower plates of a universal testing machine, and a compressive load was applied at a constant speed of (10±2) mm / min. The compressive stress was recorded when the specimen's compression deformation reached 10%, and calculated using the formula σ. 10 The compressive strength is calculated as % = F / A, where F is the load when the compressive deformation is 10% and A is the initial compressive area of the specimen.
[0074] Table 1. Performance test data of the examples and comparative examples
[0075] The embodiments of this invention exhibit significant and systematic advantages over the comparative examples in the trade-off curves of flame retardancy and mechanical properties. Specifically, all indicators related to heat release, mass loss, and flame spread consistently converge within the A2 grade judgment boundary, and the char retention capacity remains consistently high. In contrast, the comparative examples, lacking any one of the following components—dopamine modification, silane coupling, phosphorus-nitrogen expansion layer, or specific reinforcing barrier phase—show a clear pattern of progressively deteriorating fire resistance indicators, even exceeding the acceptable threshold overall. Simultaneously, with the gradient change in the composition of the inorganic composite phase, the inverse correlation between thermal conductivity and compressive strength remains within a reasonable engineering range, without any abnormal phenomenon of sudden changes in other properties due to extreme optimization of a single performance. This series of gradual changes, fully in line with the laws of materials science, fully demonstrates the synergistic positive effect of the multi-scale interface modification strategy of this invention in coordinating low weight loss and high char layer stability.
[0076] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A high-char-forming, low-weight-loss A2-grade fireproof and heat-insulating board, characterized in that, Based on parts by weight, it includes the following raw materials: 100 parts of high carbon residue polyurethane organic matrix and 44.0-52.5 parts of composite reinforcing component; The high carbon residue polyurethane organic matrix is formed by reacting the following raw materials in parts by weight: 35-50 parts aromatic polyester polyol, 20-35 parts polyether polyol, 8-18 parts phosphorus-containing aromatic polyol, 85-125 parts polyphenyl polymethylene polyisocyanate, 1.0-2.5 parts silicone oil foam stabilizer, 0.15-0.45 parts tertiary amine catalyst, and 0.05-0.20 parts organotin catalyst; The composite reinforcing component is prepared from the following raw materials: 78-86 parts of inorganic composite filler, 8.5-11.0 parts of mineral fiber reinforcing phase, 4.0-6.5 parts of nano-inorganic reinforcing phase, 2.4-3.6 parts of layered inorganic barrier phase, 0.8-1.6 parts of dopamine hydrochloride, 1.0-2.2 parts of γ-aminopropyltriethoxysilane, 3.0-6.0 parts of ammonium polyphosphate, and 2.0-5.0 parts of melamine cyanurate. The preparation method of the composite reinforcing component includes the following steps: S1. Dry the inorganic composite filler, mineral fiber reinforced phase, nano-inorganic reinforced phase and layered inorganic barrier phase at 105-120℃ for 2-4 hours, cool to 20-30℃, add 60-90 parts of ethanol and 20-40 parts of deionized water, and disperse at 800-1200r / min for 30-60min to obtain an inorganic multiphase dispersion. S2. Add the dopamine hydrochloride to the inorganic multiphase dispersion, adjust the pH of the system to 8.3-8.8, and stir for 2-4 hours at 25-35℃ and 600-900r / min to obtain the dopamine-modified inorganic multiphase dispersion. S3. Add the γ-aminopropyltriethoxysilane to the dopamine-modified inorganic multiphase dispersion, adjust the pH of the system to 4.2-5.2, and stir for 2-3 hours at 55-70℃ and 700-1000r / min to obtain the reaction solution. S4. Add the ammonium polyphosphate and melamine cyanurate to the reaction solution, stir for 1-2 hours at 60-75℃ and 600-900 r / min, filter, wash the filter cake with ethanol 2-3 times, vacuum dry at 70-85℃ for 6-10 hours, pulverize and pass through an 80-120 mesh sieve to obtain the composite reinforcing component. The inorganic composite filler comprises, by weight, 35-45 parts aluminum hydroxide, 20-30 parts magnesium hydroxide, 12-22 parts light calcium carbonate, 8-16 parts wollastonite powder, and 3-8 parts hollow glass microspheres. The mineral fiber reinforcing phase is basalt fiber; The nano-inorganic reinforcing phase is nano-silica; The layered inorganic barrier phase is montmorillonite.
2. The high char-forming, low-weight-loss A2-grade fireproof and heat-insulating board according to claim 1, characterized in that, The silicone oil-based foam stabilizer is an organosilicon-polyether copolymer foam stabilizer; The tertiary amine catalyst is one or a combination of two or more of the following: triethylenediamine, N,N-dimethylcyclohexylamine, pentamethyldiethylenetriamine, and N,N-dimethylbenzylamine. The organotin catalyst is one or a combination of two or more of stannous octoate, dibutyltin dilaurate, and dibutyltin diacetate.
3. A method for preparing a high-char-forming, low-weight-loss A2-grade fireproof and heat-insulating board as described in any one of claims 1-2, characterized in that, Includes the following steps: A1. Mix the aromatic polyester polyol, polyether polyol, phosphorus-containing aromatic polyol, silicone oil foam stabilizer, tertiary amine catalyst, organotin catalyst and 1.0-2.5 parts of deionized water at 20-30℃ and 800-1200r / min for 3-8min to obtain polyurethane component A. A2. Add the composite reinforcing component to the polyurethane component A, and disperse it at 20-30℃ and 1000-1500r / min for 5-12min to obtain a slurry containing the composite reinforcing component A; A3. Add the polyphenyl polymethylene polyisocyanate to the A component slurry containing the composite reinforcing component, and mix at 1500-2200 r / min for 10-25 s to obtain the foaming reaction material; A4. Pour the foaming reaction material into the mold, foam and cure at 35-55℃ for 20-40 minutes, and after demolding, post-cur at 60-80℃ for 4-8 hours to obtain the high char-forming, low weight loss A2 grade fireproof insulation board.
4. The method for preparing a high-char-forming, low-weight-loss A2-grade fireproof and heat-insulating board according to claim 3, characterized in that, The inner surface temperature of the mold in A4 is 35-45℃, and the casting density of the foaming reactant is controlled at 60-70 kg / m³. 3 The thickness of the sheet material obtained after demolding is 30-80mm.
5. The method for preparing a high-char-forming, low-weight-loss A2-grade fireproof and heat-insulating board according to claim 3, characterized in that, The composite reinforcing component in A2 is added to the polyurethane component A in 2-3 portions, and after each addition, it is dispersed for 2-5 minutes at 1000-1500 r / min.
Citation Information
Patent Citations
Homogeneous non-combustible polyurethane foam heat insulating material and preparation method thereof
CN108774306A
Fiber-reinforced polyurethane composite material applied to aluminum alloy doors and windows and preparation method of fiber-reinforced polyurethane composite material
CN121427053A